A Defective Circulating Mitochondrial Bioenergetics Profile Reflects the Hepatic One and Outlines Genetic MASLD - Erika Paolini; Miriam Longo; Marica Meroni; Paola Podini; Marco Maggioni; Angelo Quattrini; Anna Ludovica Fracanzani; Paola Dongiovanni (Antioxidants)
Genetics and mitochondrial (mt) dysfunction contribute to metabolic dysfunction-associated steatotic liver disease (MASLD). Recently, we demonstrated that the co-presence of PNPLA3, TM6SF2 and MBOAT7 polymorphisms predisposes to disease progression in MASLD patients and that their deletion triggers mt maladaptation in vitro. Here, we deepened the impact of the silencing of these genes on mt dynamism and respiration by reintroducing TM6SF2 and/or MBOAT7 wild-type proteins in deleted cells through lentiviral infection. Since hepatic mt bioenergetics is impaired in MASLD, in the attempt to identify a non-invasive signature, we then compared the enzymatic mt activity of seahorses, which was assessed in liver biopsies and peripheral blood mononuclear cells (PBMCs) of biopsy-proven MASLD patients (n = 44; Discovery cohort) stratified according to the number of the three at-risk variants (3NRV). Concerning the in vitro results, the rescue of MBOAT7 and/or TM6SF2 wild-type proteins resulted in the assembly of spaghetti-shaped mitochondria with improved oxidative phosphorylation (OXPHOS) capacity. In the Discovery cohort, the hepatic bioenergetic profile fully reflected that in PBMCs and was impaired especially in 3NRV carriers. A lowered serum respiration rate was confirmed in noninvasively assessed MASLD (n = 45; Fibroscan-MASLD cohort), while it did not change in unrelated liver disease patients (n = 45). In summary, we firstly demonstrated that mt circulating respirometry reflects that in liver and is specific in defining genetic MASLD.